The Spectacular Nature of the Election Campaign in Georgia Abstract - Melikidze, Giorgi (Politics / პოლიტიკა, 2017)
the last quarter of the 20 th century the world party system and its political campaign have suffered important changes and the process Americanization began. The majority of the Western European parties are based on the solid ideological basis and representation of the interests of electorate. In the new democracies political parties are characterized with weak organization and special personalization. Moreover, in these countries the fragile ideological grounds of political parties conditioned spectacular character of election campaign. Researchers term such modification of election campaign “Carnivalization”. The present paper aims to determine how political personification determines spectacular character of the electoral campaign. In the 1990s the weak representation of the Georgian political parties has plaid determining role in terms of transformation of political campaign. Therefore, after the Rose Revolution of 2003 the “Carnivalization” process of election campaign became active. The study is based on the following qualitative research methods: a). Expert interviews with political consultants; b). In-depth interviews with representatives of political parties; g). In-depth interviews with the selected electorate.